A study on the effect of site response on California seismic hazard map assessment - Gallahue, Molly M.; Salditch, Leah; Lucas, Madeleine C.; Neely, James; Stein, Seth; Abrahamson, Norman; Williams, Tessa; Hough, Susan E. (Frontiers in Earth Science, 2022)
Seismologists have long appreciated the influence of near-surface geology, in particular low-impedance sediment layers, on earthquake ground motions at frequencies of engineering concern. Modern ground motion models (GMMs) commonly account for site effects using terms based on VS30, the time-averaged shear-wave velocity in the upper 30 m of the Earth’s surface. In this study, we use published GMMs with VS30-based site terms to incorporate site effects in probabilistic seismic hazard maps for California. At the long periods (1-5 s) that affect tall buildings, the mapped hazard is amplified by factors of 1-3 at many sites relative to the maps calculated for a reference site condition. However, at the short periods that control peak ground acceleration (PGA) and thus affect smaller structures, only negligible effects occur due to non-linear deamplification of strong ground motion at high frequencies. In some instances, non-linear terms are strong enough to deamplify the reference map values. We explore the implications of these results for the evaluation of hazard maps. Because site effects do not change the map appreciably at high frequencies, we can exclude site response as an explanation for why the maps overpredict historically observed shaking as captured by the California Historical Intensity Mapping Project (CHIMP) dataset. These results should be generalizable to areas beyond California.